ANALYSIS OF DAMAGE TO THE CLUTCH SYSTEM IN THE 2003 TOYOTA AVANZA ENGINE - Galang Tegar Darmawan; Sulaeman Deni Ramdani; Suadi (Jurnal Pendidikan Teknik Mesin, 2023)
Motorized vehicles have main parts that must be considered by the driver, especially in operation. One of them is the clutch system. The purpose of this research is to analyze the damage to the clutch. This research was conducted at the vocational and productivity training center in Bandung (BBPVP Bandung). In this study using the method of observation and literature study. For data collection techniques using observation techniques, as well as using a vernier caliper. The object of this research is the Toyota Avanza 2003 engine. The results of this study inform that the damage that often occurs to the clutch unit there are three components, namely clutch lining, clutch sun and deklaher. Problems that cause clutch damage include frequently stepping on and releasing the clutch pedal roughly, always half-stepping on the clutch when the car is on an uphill or traffic jam, the habit of stepping on the clutch pedal when the car is running and shifting gears in the transmission gears not in stages according to position